1996
DOI: 10.1029/95jd03348
|View full text |Cite
|
Sign up to set email alerts
|

A reevaluation of the open ocean source of methane to the atmosphere

Abstract: Seawater and atmospheric methane (CH4) mixing ratios were measured on five cruises throughout the Pacific Ocean from 1987 to 1994 to assess the magnitude of the ocean‐atmosphere flux. The results showed consistent regional and seasonal variations with surface seawater concentrations ranging from 1.6 to 3.6 nM and saturation ratios ranging from 0.95 to 1.17. The equatorial Pacific Ocean was supersaturated with respect to atmospheric CH4 partial pressures, while areas outside the tropics often were undersaturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
114
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 52 publications
12
114
7
Order By: Relevance
“…It appears that most studies rely on the work of Ehhalt (1974), where the value was estimated on the basis of the measurements done by Swinnerton and co-workers (Lamontagne et al, 1973;Swinnerton and Linnenbom, 1967) for the open ocean, combined with purely speculated emissions from the continental shelf. Based on basin-wide observations using updated methodologies, three studies found estimates ranging from 0.2 to 3 Tg CH 4 yr −1 (Conrad and Seiler, 1988;Bates et al, 1996;Rhee et al, 2009), associated with supersaturations of surface waters that are an order of magnitude smaller than previously estimated, both for the open ocean (saturation anomaly ∼ 0.04, see Rhee et al, 2009, Eq. 4) and for the continental shelf (saturation anomaly ∼ 0.2).…”
Section: Oceanic Sourcesmentioning
confidence: 97%
“…It appears that most studies rely on the work of Ehhalt (1974), where the value was estimated on the basis of the measurements done by Swinnerton and co-workers (Lamontagne et al, 1973;Swinnerton and Linnenbom, 1967) for the open ocean, combined with purely speculated emissions from the continental shelf. Based on basin-wide observations using updated methodologies, three studies found estimates ranging from 0.2 to 3 Tg CH 4 yr −1 (Conrad and Seiler, 1988;Bates et al, 1996;Rhee et al, 2009), associated with supersaturations of surface waters that are an order of magnitude smaller than previously estimated, both for the open ocean (saturation anomaly ∼ 0.04, see Rhee et al, 2009, Eq. 4) and for the continental shelf (saturation anomaly ∼ 0.2).…”
Section: Oceanic Sourcesmentioning
confidence: 97%
“…The ocean surface acts as a net source of atmospheric CH 4 , although its release is minor compared with natural emissions on land (Cicerone and Oremland, 1988). Estimates of annual oceanic CH 4 emission vary greatly between 0.4 (Bates et al, 1996) and 11-18 Tg C y À1 (Bange et al, 1994) and part of this uncertainty could be associated with low spatial resolution. Regional CH 4 emissions fluctuate widely; for example, surface waters of subtropical oceanic gyres are almost in equilibrium (100%) or slightly supersaturated (>100%) with the atmosphere (Holmes et al, 2000) whereas coastal areas can attain up to 500% surface CH 4 saturation (Sansone et al, 2001;Rehder et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 fluxes were higher at stations located at the PF and A3, where phytoplanktonic blooms were observed (see Table 2), but the tendency was the reverse for N 2 O, with an influx into the aforementioned stations. CH 4 emission rates during this study were higher than previously measured (Table 2), with a range of 0.1 to 3.0 µmol m −2 d −1 for the Pacific Ocean (Bates et al, 1996;Holmes et al, 2000;Sansone et al, 2001) and 0.5 to 9.7 µmol m −2 d −1 for the Atlantic Ocean (Oudot et al, 2002;Forster et al, 2009). In the South Pacific ocean (10 • -64 • S, 140 • E), crossing the PF, Yoshida et al (2011) reported CH 4 fluxes ranging from 2.4 to 4.9 µmol m −2 d −1 .…”
Section: Ch 4 and N 2 O Emission In The Southern Oceanmentioning
confidence: 40%
“…In different regions of the Southern Ocean, the surface layer is permanently supersaturated with CH 4 (Bates et al, 1996;Tilbrook and Karl, 1994;Yoshida et al, 2011), but this is not the case for N 2 O, which may occur in either underor supersaturated conditions (Law and Ling, 2001;Rees et al, 1997;Chen et al, 2014). Aside from physical processes affecting GHG concentrations in the water column and their concomitant air-sea fluxes, the concentrations also depend on organic matter (OM) availability and oxygen levels, which determine whether aerobic or anaerobic respiration occurs (Codispoti et al, 2001;Reeburgh, 2007).…”
mentioning
confidence: 99%